Children's Interpretation of Sentences Containing Multiple Scalar Terms. (23rd November 2021) - Bill, Cory; Pagliarini, Elena; Romoli, Jacopo; Tieu, Lyn; Crain, Stephen
Abstract: Sentences containing the scalar term "some", such as "The pig carried some of his rocks", are usually interpreted as conveying the scalar inference that the pig did not carry all of his rocks . Previous research has reported that when interpreting such sentences, children tend to derive fewer of these scalar inferences than adults ( Noveck (2001) ; Papafragou & Musolino (2003) ; Guasti et al. (2005), among others). One approach to explaining these results contends that children have difficulties accessing the alternative sentences involved in the derivation of such scalar inferences. This 'Alternatives-based' approach raises the possibility that children's performance may improve if certain scalar terms are presented together in the same sentence, for example, if a sentence contains both an existential quantifier and a universal quantifier, as in "Every pig carried some of his rocks". Such 'EverySome' sentences have been associated with the inference that not every pig carried all of his rocks, as well as the stronger inference that none of the pigs carried all of his rocks (see Chemla & Spector (2011), among others). We present two experiments that explore the possibility that children might more readily derive scalar inferences from sentences containing such a combination of scalar terms. Experiment 1 investigates children's interpretation of sentences containing only the quantifier some and replicates the previously established finding of fewer inference-based interpretations by children compared to adults. Experiment 2 explores children's interpretation of sentences in which "some" is embedded under "every", and reveals that adults and children access inference-based interpretations of such sentences at similar rates. Moreover, adults and children appear to differ with regards to which of the two possible inferences their interpretations are based on. We discuss the implications of the experimental results for our understanding of children's acquisition of scalar inferences and for proposals that attempt to capture differences between adults' and children's interpretive preferences.